Conexões e desconexões – os temas da história e geografia no ensino fundamental e sua relação com a sociologia no ensino médio - Carvalho, Ana Cecília Soares (2016)
This research aims to analyze whether the content of sociology have connections with the working themes of disciplines of History and Geography (Elementary School). Starting from concept that education aims (or should aim) an integral formation of citizens, providing knowledge and reflections so that student can understand the context in which he lives, and thus transform it; we think of as the most humanistic/reflective training has been conducted in schools, especially in Elementary School and High School. For our study, the Human Sciences of Elementary School has represented here by disciplines: History and Geography, and we analyze the possibilities of these two areas of knowledge and their possible connections/interconnections with sociology. For this, we evaluated official documents and textbooks for better understand how the Social Sciences field contents has worked with our children and youth; and what are the contributions of the sociology as a discipline in the Elementary School curriculum. In our analysis we noticed some mismatches between the goals set for the History and Geography, and how these disciplines are shown in the reality work in schools, punctuating also, the intentions and interests that permeate the critical and reflexive work in schools. Faced with this scenario, we present discussions on the importance of the Human Sciences in education, the contributions and work opportunities between the History, Geography and Sociology.